2012
DOI: 10.1097/tp.0b013e3182620596
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Neurological Presentation and Severe Posttransplant Brain Injury in Patients With Acute Liver Failure

Abstract: Pretransplant neurological complications were prevalent, and severe posttransplant BI occurred at a rate of 7.8% and was significantly associated with severe pretransplant cerebral edema and postoperative international normalized ratio. Our findings support the use of pretransplant computed tomography. If severe pretransplant cerebral edema is confirmed, efforts should be made to aggressively control intracranial pressure and select a proper donor to minimize the risk of severe posttransplant BI and futile tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…However, we did not detect a poorer long-term survival in APAP patients with more advanced encephalopathy at presentation. Nonetheless, other studies have demonstrated that severe cerebral oedema is predictive of poor neurological outcomes and survival in ALF patients (20,21).…”
Section: Discussionmentioning
confidence: 97%
“…However, we did not detect a poorer long-term survival in APAP patients with more advanced encephalopathy at presentation. Nonetheless, other studies have demonstrated that severe cerebral oedema is predictive of poor neurological outcomes and survival in ALF patients (20,21).…”
Section: Discussionmentioning
confidence: 97%
“…ARI was defined as a 2‐fold or greater increase in the serum creatinine level in the first week after LT in comparison with the preoperative levels. ARI was analyzed after the exclusion of patients with pretransplant renal failure …”
Section: Methodsmentioning
confidence: 99%
“…Eight out of 61 (13%) had delayed awakening, requiring prolonged postoperative mechanical ventilation and the need of a tracheostomy. In DDLT for ALF, a relatively high incidence of recipient death due to encephalopathy has been reported . In contrast with LDLT, the reported rate of posttransplant mortality because of irreversible CE is low .…”
Section: Discussionmentioning
confidence: 99%